Проблемні аспекти встановлення предмета умисного знищення або пошкодження територій, взятих під охорону держави, та об’єктів природно-заповідного фонду - Шульга, А. М.; Shulga, A. M.; ORCID: http://orcid.org/0000-0003-3745-4869 (Вісник Кримінологічної асоціації України. - 2016. - № 2 (13). - С. 86-97, 2016)
Стаття присвячена з’ясуванню проблемних аспектів встановлення предмета умисного знищення або пошкодження територій, взятих під охорону держави, та об’єктів природнозаповідного фонду. Розглянуто точки зору щодо розуміння юридичної природи предмета злочину. Пропонується новітнє визначення поняття «предмет умисного знищення або пошкодження територій, взятих під охорону держави», та об’єктів природнозаповідного фонду. У статті робиться висновок про звуженість встановлення предметного складу умисного знищення або пошкодження територій, взятих під охорону держави, та об’єктів природнозаповідного фонду.

The current state of the environment is characterized by extremely negative indicators. We can change the situation by mobilizing the efforts of the entire society and the state. The state provides steps towards ensuring adequate protection of natural resources by guaranteeing the compliance with established regulations in this area. One of these steps is to establish criminal liability for intended destruction or damaging the areas under the state protection and objects of natural and reserved fund. The issues of legal protection of natural resources were and are the interests of the following scholars in the law field: V. I. Andreitsev, Yu. S. Bohomiakov, M. M. Brynchuk, T. D. Bushuieva, V. P. Vladymyrov, S. B. Havrysh, A. P. Hetman, P. S. Dahel, O. V. Dubovyk, O. O. Dudorov, Ye. N. Zhevlakov, O. M. Kovtun, Z. H. Korcheva, S. M. Kravchenko, U. Ya. Krastynsh, B. M. Leontiev, N. O. Lopashenko, Yu. M. Liapunov, V. K. Matviichuk, P. S. Matyshevskyi, V. O. Navrotskyi, L. F. Povelitsina, B. H. Rozovskyi, V. P. Samokysh, Yu. S. Shemshuchenko, N. H. Shymbareva, M. V. Shulha and other experts in criminal, environmental law and criminology. The objective of the research is to address the problematic aspects of establishing the object of intended destruction or damaging the areas under the state protection and objects of natural and reserved fund. The issue of determining the object of the specific crime remains today one of the most urgent problems of the theory of national criminal law and is considered as one of the most difficult. The crime under the Art. 252 of the Criminal Code of Ukraine belongs to the socalled “substantive offenses”. Accordingly, to implement the correct qualification and to establish the grounds of criminal liability for intended destruction or damaging the areas under the state protection and objects of natural and reserved fund it is necessary to define the object of the crime. Different points of view on the definition of the object of the offense under the Art. 252 of the Criminal Code of Ukraine and its narrowness and limitation complicate the application of this norm in practice. Therefore, the mandatory is such a definition of the object of intended destruction or damaging the areas under the state protection and objects of natural and reserved fund that would satisfy the requirements of a law enforcement official. First, absence of a single point of view in determining and understanding the essence of the object of a crime does not allow simply to establish any object of the specific crime. Second, the offense under the Art. 252 of the Criminal Code of Ukraine “Intended Destruction or damaging the Areas under the State Protection and Objects of Natural and Reserved Fund” refers to the group of objective crimes, which makes it obligatory establishment of its object. Third, due to the fact that the disposition of the Art. 252 of the Criminal Code of Ukraine contains a reference to only two elements of a single natural system – the national ecological network. Therefore, it is appropriate to admit the object of this crime not a part of a single ecological system, but the whole natural complex – ecological network.

Статья посвящена выяснению проблемных аспектов установления предмета умышленного уничтожения или повреждения территорий, охраняемых государством, и объектов природнозаповедного фонда. Рассмотрено точки зрения относительно понимания юридической природы предмета преступления. Предлагается новое определение понятия «предмет умышленного уничтожения или повреждения территорий, охраняемых государством, и объектов природнозаповедного фонда». В статье делается вывод об ограниченности определения предметного состава умышленного уничтожения или повреждения территорий, охраняемых государством, и объектов природнозаповедного фонда.
Problematic aspects of establishing the object of intended destruction or damaging the areas under the state protection and the objects of natural and reserved fund
Проблемные аспекты установления предмета умышленного уничтожения или повреждения территорий, взятых под охрану государства и объектов природно-заповедного фонда
Шульга, А. М. Проблемні аспекти встановлення предмета умисного знищення або пошкодження територій, взятих під охорону держави, та об’єктів природно-заповідного фонду / Андрій Михайлович Шульга // Вісник Кримінологічної асоціації України. - 2016. - № 2 (13). - С. 86-97.
Keywords: Кримінальне право. Criminal Law. Уголовное право; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; об’єкти природнозаповідного фонду; національна екологічна мережа; crime object; areas under the state protection; objects of the natural and reserved fund; national ecological network; предмет преступления; территории, охраняемые государством; охраняемые государством территории; объекты природнозаповедного фонда; национальная экологическая сеть; умисне знищення або пошкодження; території, взяті під охорону держави; предмет злочину